NURSING PROTOCOLS IN PRIMARY HEALTH CARE: INSTRUMENT FOR QUALITY OF CARE - Márcia Cristina Cid Araújo; Sonia Acioli; Mercedes Neto; Halene Cristina Dias de Armada e Silva; Gláucia Bohusch; Flávia Nascimento da Rocha; Thiago Wendel Gonzaga da Silva (Universidade Federal do Paraná, 2020)
Objective: to analyze the nursing protocols as a possible instrument for the quality for the nurse's practice in Primary Health Care. Method: a descriptive and qualitative study, carried out by means of documentary analysis and semi-structured interviews, with 14 nurses from Metropolitan Regions I and II in the state of Rio de Janeiro. Bardin's thematic content analysis was used for data treatment. Results: the category analyzed in this article was the "place of care", which addresses the quality of care in nurses' actions and its importance for the profession. Conclusion: collective and dialogical constructions are motivating factors for the elaboration of local protocols. In addition to being a permanent education strategy, nurses recognized the protocols as tools for decision-making, providing them with technical and ethical support, which greatly contributes to the construction of knowledge and to the development of good nursing practices.